Pengaruh Mata Kuliah Etika Bisnis Islam terhadap Minat Menjadi Entrepreneur (Studi Pada : Mahasiswa Program Studi Ekonomi Syariah Institut Pesantren Sunan Drajat) - Siswadi Siswadi; Lidya Frasisca Ellyna (Al-Maqashid: Journal of Economics and Islamic Business, 2023)
The Islamic Business Ethics course applied in higher education aims to provide knowledge about ethics in business in accordance with sharia so that students have the ability to run a business in accordance with what is ordered in Islam, so that when students have graduated from their college have the provisions to open a business in sharia. Interest in becoming an entrepreneur includes a person's interest in creating a business by looking at the opportunities that are around and daring to take risks that may occur in running a business. This study aims to answer, describe and analyze the research problem formulation which consists of: 1. How is the Islamic Business Ethics Course in the Sunan Drajat Islamic Boarding School College? How are students interested in becoming entrepreneurs? and Is there any influence between Islamic Business Ethics Course on students' interest in becoming Entrepreneurs? The research method used in this study is a quantitative research method with the type of field research. The population in this study were all students of the 2019 Islamic Economics study program who had taken the Islamic Business Ethics course. The research instruments used were: questionnaires or questionnaires and interviews. The results of this study concluded that: (1) Islamic Business Ethics Course had a significant effect on the interest in becoming an entrepreneur. The influence of Islamic Business Ethics Course is 34.8% and the remaining 65.2% is influenced by other variables. (2) Interest in becoming an entrepreneur based on the correlation results stated that the value of interest in being an entrepreneur in students was 0.348 or 34, 8%. (3) There is a significant effect on the variable of Islamic Business Ethics Course (X) on the interest in becoming an Entrepreneur (Y) based on the calculation results obtained a correlation coefficient value of 0.348 indicating the correlation value ranges from -1 to +1 (-1≤ r 1) means the level of correlation shows moderate. So, according to the test criteria, Ha is accepted and Ho is rejected, which means that the hypothesis shows that there is a significant relationship between the Islamic Business Ethics Course and the interest in becoming an Entrepreneur of the 2019 Islamic Economics Study Program students at the Sunan Drajad Islamic Boarding School.